2015
DOI: 10.1016/j.humpath.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous and lymphocytic interstitial lung disease: a spectrum of pulmonary histopathologic lesions in common variable immunodeficiency—histologic and immunohistochemical analyses of 16 cases

Abstract: Common Variable Immunodeficiency (CVID) is a primary immunodeficiency of unknown etiology characterized by low serum IgG, a decreased ability to make specific antibodies, and variable T cell defects. Approximately 20% of patients with CVID develop clinical evidence of a diffuse parenchymal lung disease with a constellation of histopathological findings termed granulomatous and lymphocytic interstitial lung disease (GLILD). In this study, we characterized the histological and immunohistochemical features in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
116
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 39 publications
11
116
1
1
Order By: Relevance
“…These features are consistent with the FB and LIP patterns that had been ascribed to GLILD a decade prior [2••]. In addition to lymphocytic inflammation, non-necrotizing granulomata were also present in 15/16 cases examined [22•]. These were randomly distributed throughout the lung parenchyma in a basilar distribution, varied from being well-formed to poorly formed and consisted of epithelioid histiocytes with occasional multinucleated giant cells.…”
Section: Discussion and Literature Reviewsupporting
confidence: 77%
See 2 more Smart Citations
“…These features are consistent with the FB and LIP patterns that had been ascribed to GLILD a decade prior [2••]. In addition to lymphocytic inflammation, non-necrotizing granulomata were also present in 15/16 cases examined [22•]. These were randomly distributed throughout the lung parenchyma in a basilar distribution, varied from being well-formed to poorly formed and consisted of epithelioid histiocytes with occasional multinucleated giant cells.…”
Section: Discussion and Literature Reviewsupporting
confidence: 77%
“…Recently, Rao and colleagues thoroughly detailed the histopathological and immunohistochemical features of VATS-guided or open lung biopsies obtained from 16 CVID patients with GLILD [22•]. Nodular peribronchiolar and diffuse interstitial lymphocytic inflammation was demonstrated in all cases with expansion of the interstitium occurring in severe cases.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of GLILD in PID patients points to a poorer prognosis and increases the prevalence of lymphoproliferative disorders [110]. The finding of interstitial fibrosis (with or without architectural remodeling) requires additional study for its effect on prognosis [111]. The typical imaging pattern of ILD in PAD is a generalized diffuse reticular change and consolidation, with or without a groundglass appearance, predominantly in the lower lobe.…”
Section: Interstitial Lung Diseasementioning
confidence: 99%
“…Rao et al [111] evaluated CVID patients and reported OP in 87.5%, mostly in mild forms of the disease. Pulmonary function tests reveal a mild-to-moderate restrictive pattern.…”
Section: Organizing Pneumoniamentioning
confidence: 99%